Kepastian Hukum atas Kepemilikan Tanah Pasca Penghapusan Surat Keterangan Tanah (SKT) dalam Perspektif Hukum Pertanahan Nasional - Absi, Warmiyana Zairi (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
The Land Certificate has been one of the documents used to prove control over land parcels in Indonesia. However, with the policy of abolishing SKT as an administrative requirement in the land certification process, concerns arise regarding legal certainty for land owners who previously only had a Land Certificate. This research aims to examine the legal consequences of the abolition of the Land Certificate and how the guarantee of legal certainty over land ownership can still be upheld in the perspective of National Land Law. This research uses normative juridical method with statutory approach and legal certainty theory. The results of the study show that although the Land Certificate is not a strong proof of ownership according to positive law, its abolition requires a transitional scheme and legal protection that ensures that the community's rights to land are still recognized. The rearrangement of the mechanism for proving land history and the expansion of the role of local governments are crucial in realizing justice and legal certainty in the land certification process.